Peran Pustakawan pada Layanan Referensi di Unit Pelaksana Administrasi Perpustakaan Isi Padang Panjang dalam Memenuhi Kebutuhan Informasi Pemustaka - Fadya Ramadhany Budyman; Desriyeni; Aivan Sondra (Jurnal Syntax Admiration, 2024)
Libraries as information centers have a crucial role in education, research, and community literacy development. In the digital era, libraries are required not only to provide access to information, but also services that meet the needs of users. One of the important services is the reference service, which serves as a link between the user and the information needed. Librarians play a vital role in this, not only as custodians of collections, but also as educators and facilitators. At the UPA Library of the Indonesian Institute of the Arts (ISI) Padang Panjang, the reference service supports the needs of students, lecturers, and researchers. However, limited human resources are a challenge, with only two librarians, one of whom is active in the service. This study aims to examine the role of librarians in reference services, focusing on their role as educators and trainers of information literacy as well as facilitators of learning and research. Librarians are expected to guide users in choosing and using information effectively, especially in the context of abundant digital information. They also function as facilitators in supporting the learning and research process, especially for students in the field of arts and culture. The research method used is qualitative with in-depth interviews to understand the roles and challenges of librarians. The results of the study are expected to provide a clear picture of the role of librarians in the UPA ISI Padang Panjang Library and recommendations to improve services to meet the information needs of users, so that libraries can contribute more to education and research.